Children and Domestic Violence Services (CADVS) Study: Co-Occurring Intimate Partner Violence and Child Maltreatment in the United States, 2003-2004 - Kelleher, Kelly ([Verlag nicht ermittelbar], 2012)
The goal of the Children and Domestic Violence Services (CADVS) was to provide a rich description of the variation in state, county, and local policies and practices related to the issue of co-occurring child maltreatment and domestic violence. The CADVS collected state and local contextual data via telephone interviews with Child Welfare Services (CWS) and Domestic Violence Services (DVS) agencies to provide information on policies and practices for domestic violence and child maltreatment relevant to (1) child placement in out-of-home care, and (2) the use of family preservation services and residential stability among these families in the child welfare system. These contextual data then were linked to the National Survey of Child and Adolescent Well-Being (NSCAW), the parent study and longitudinal survey of youth, parents and other caregivers, child welfare workers, and teachers, which provided indicators needed for child characteristics, caregiver characteristics, child placement career, and mental health services. For this supplement to the NSCAW, a snowball interviewing technique was used. On the front end, CWS agencies were sent an overview letter about the study. Initial contacts were interviewed and, if appropriate, were asked to nominate and facilitate introductions to other contacts to locate the best informant for each interview domain. Each CWS informant then was asked to provide contact information for the local provider(s) of DVS, including a contact name, if possible. Data from these respondents was used to assess interagency agreement on local policies and practices. Identified DVS representative agencies then received the same introductory letters about the study sent to the CWS agencies. A snowball interviewing technique was again used to identify informants in each agency who would be best able to answer questions regarding related services. The key informants from both the CWS and DVS agencies received additional information on the study, an interview summary, and a copy of the informed consent agreement. Interview data then were collected from CWS and DVS agency informants by telephone. This process began in January 2003 and was completed in February 2004. The need for multiple informants to complete different survey modules for each agency resulted in a total of 860 interviews with 406 interviewees. The data file contains 89 cases and 1,209 variables where each case represents an agency. The measures for CADVS were an amalgamation of (1) child, caregiver and family measures collected in NSCAW and (2) contextual data on policy/practices collected through surveys of states, counties, and localities developed for this particular study. These include such issues as funding, policies regarding the reporting of child maltreatment, referrals made regarding the domestic violence victim or her children, what services are available for children of domestic violence victims, types of service providers, locations of mental and physical health evaluations, and types of training which CWS and DVS staff received.